1977/78 maha kannayē vī vagā ṇaya aya vīma piḷibanda samīkṣaṇaya : polonnaruva Distrikkaya - Da Alvis, Lāl (Study papers., 1979)
Study on repayment of agricultural credit in Polonnaruwa District, Sri Lanka.